The Role of Jurisprudence in The Application of Substitute Heirs Concept in Indonesia - Burhanuddin, Burhanuddin (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2023)
The position of successor heirs in Indonesia lacks clear legal regulations, necessitating reliance on jurisprudence as a guiding framework for law enforcement officials. This study explores the benefits of jurisprudence in shaping the development of successor heirs' rights in Indonesia. Employing a normative juridical approach, the research relies on descriptive analysis and library research. The findings highlight two significant advantages of jurisprudence in this context. Firstly, jurisprudence clarifies material legal aspects by integrating provisions concerning successor heirs into Indonesia's legal system, notably through Article 185 of the Compilation of Islamic Law. This integration fosters legal coherence and clarifies successor heirs' rights and obligations. Secondly, jurisprudence aids in formal legal aspects by ensuring the completeness of administrative data for inheritance litigation in the Religious Court. This enhances procedural fairness and facilitates efficient resolution of cases involving successor heirs. Jurisprudence contributes to legal certainty, fairness, and societal benefits in inheritance matters. Its role in interpreting and supplementing existing laws underscores its importance in navigating legal complexities and ensuring justice for successor heirs in Indonesia.Posisi ahli waris pengganti di Indonesia membutuhkan perhatian mendalam karena ketidakjelasan dalam peraturan hukum yang mengaturnya. Kurangnya regulasi secara eksplisit mengenai ahli waris pengganti menuntut pihak penegak hukum untuk mengandalkan sumber hukum lain sebagai pedoman dalam penyelesaian kasus terkait. Yurisprudensi menjadi penting dalam membantu hakim memutuskan kasus-kasus semacam itu. Penelitian ini bertujuan untuk menggali manfaat kaidah yurisprudensi terhadap ahli waris pengganti dalam konteks perkembangan hukum di Indonesia, menggunakan pendekatan yuridis normatif serta metode analisis deskriptif dan penelitian perpustakaan. Hasilnya menunjukkan bahwa kaidah-kaidah hukum yurisprudensi memberikan kejelasan terhadap kedudukan ahli waris pengganti dalam sistem hukum Indonesia, termasuk melalui Pasal 185 Kompilasi Hukum Islam. Selain itu, yurisprudensi juga membantu dalam aspek formalitas hukum dengan memastikan kelengkapan data administratif untuk proses peradilan di Pengadilan Agama. Dengan demikian, yurisprudensi dianggap dapat memberikan kepastian, keadilan, dan manfaat hukum bagi masyarakat terkait kasus kewarisan yang melibatkan ahli waris pengganti